Burnout and Spiritual Coping Strategies Among Islamic Religious Education Teachers in East Java - Rosyadi, Imron; Dani Hermawan (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2026)
Teacher burnout is a growing concern because prolonged occupational demands can weaken emotional resources, professional commitment, and well-being. This issue is especially relevant for Islamic Religious Education (IRE) teachers, who also carry moral responsibilities for students’ religious character development. Yet, limited research explains how these subject-specific responsibilities relate to spiritual coping. This study used an explanatory sequential mixed-methods design involving 215 IRE teachers from public senior high schools and vocational schools in East Java, Indonesia. Participants were recruited through network-based non-probability sampling via professional teacher networks and MGMP communities. Quantitative data assessed emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA), followed by interviews with 12 teachers from the high-EE group. Results showed that 42.3% of participants had high EE and 42.8% had low PA, indicating substantial emotional depletion and reduced professional accomplishment among teachers in the participating network. Qualitative findings identified tawakkul as cognitive reappraisal, dhikr and shalat as emotional regulation, and sabr as pedagogical endurance. These practices supported meaning and professional commitment but did not remove occupational strain. Spiritual coping should therefore complement organisational interventions, including manageable workloads, supportive leadership, and clearer professional roles, to promote teacher well-being.